Predictive Factors for Recovery Time in Conceived Women Suffering From Moderate to Severe Ovarian Hyperstimulation Syndrome - Huang, Kai; Shi, Ying; Chen, Gezi; Shi, Hao; Zhai, Jun (Frontiers in Endocrinology, 2022)
Objective This study aimed to evaluate potential predictors for recovery time in pregnant patients with moderate to severe ovarian hyperstimulation syndrome (OHSS). Methods A total of 424 pregnant patients with moderate to severe OHSS who underwent in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) were retrospectively identified. The clinical features and laboratory findings within 24 h after admission were collected. Treatment for OHSS was carried out according to standard procedures, including fluid replacement therapy, human albumin, aspirin, low-molecular-weight heparin, and paracentesis, when necessary. Patients were discharged from the hospital when the tmorning hematocrit was <40% and no obvious clinically relevant symptoms existed, such as abdominal distension, abdominal pain, and shortness of breath. Meanwhile, ultrasound indicating little pleural or abdominal effusion and biochemical abnormalities returning to normal were required. Spearman’s correlation analysis was used to assess the association between the blood-related parameters and recovery time. Multiple linear regression models were used to assess the relationship between the clinical or laboratory parameters and recovery time. Results The median recovery time of these patients was 11 days. In Spearman’s correlation test, leukocytes, hemoglobin, platelets, hematocrit, creatinine, prothrombin time (PT), fibrinogen (Fib), D-dimer, and fibrinogen degradation products (FDPs) were positively correlated with recovery time. On the other hand, albumin and thrombin time (TT) were negatively correlated with recovery time. Multiple linear regression analysis showed that polycystic ovary syndrome (PCOS), hemoglobin, platelets, albumin, and Fib were significantly associated with the recovery time of patients with OHSS (p = 0.023, p < 0.001, p = 0.007, p < 0.001, and p = 0.019, respectively). Conclusions In pregnant patients with OHSS, PCOS and hypoalbuminemia were associated with a significantly longer recovery time. Meanwhile, the recovery time was longer when patients have high levels of hemoglobin, platelets, and Fib.